HARMONIC ANALYSIS FOR SOLAR PV ARRAY FED VSI USING CURRENT CONTROLLER - Raj, T.Gowtham; Somasundaram, P.L. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
A common method in the study of voltage source inverters is the hypothesis of a voltage-type input source even in the case of renewable energy (RE). The converter is supplied by an renewable energy sources, such as a Solar photovoltaic Array, the dc-link voltage is controlled by the converter with the closed loop to extract the maximum power from the solar PV. The main aim of the paper is to reduce the harmonics by the low pass filter and analyze the total harmonic distortion with current controller technique in three level voltage source inverter. The use of perturb and observe MPPT will help to produce high output efficiency from solar PV cell. The simulation result for the paper is analysed using MATLAB/SIMULINK software and the values for the total harmonic distortion is calculated